BIOLOGY OF SILKWORM Bombyx mori L. (Lepidoptera: Bombycidae) - ALVAREZ-R., J. ALONSO (Revista Colombiana de Entomología, 1993)
Being an exotic insect, the silkworm biology is little known in Colombia. A study was conducted to obtain basic information on the life cycle of this insect at the Entomology Laboratory of the Research Center "Tibaitatá", of the Colombian Agricultural Institute (ICA) at Mosquera (Cund.) (T=24°C; R.H.=70-80%). The –lean duration, in days, of the egg and the pupal stages was 11.0 and 15.40, respectively. The larvae passed through live instars; the mean duration, in days, of each instar, was 4.60; 6.00; 6.06; 6.47 and 9.87, respectively; for a total of 33 days. The total duration in days, from egg to adult, was 59.40. The mean head capsule width for each instar was 0.54; 1.02; 1.65; 2.51 and 3.58 mm, and the growth ratio was 1.86; 1.62; 1.52 and 1.43.